2020
DOI: 10.1111/jop.13109
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation sequencing assay in salivary gland cytology: A pilot study

Abstract: Background Preoperative diagnosis of salivary gland tumors (SGTs) by fine‐needle aspiration (FNA) cytology is challenging. Next‐generation sequencing (NGS)‐based assays for somatic mutations have a great advantage in that a large number of genes can be analyzed simultaneously. Although NGS may have an enormous diagnostic potential in cytology, to our knowledge, the significance of NGS in SGT cytology remains to be clarified. Methods In this pilot study, we retrospectively examined 32 frozen SGT samples obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…5 Next-generation sequencing (NGS) is a relatively new high-throughput, highly sensitive molecular technology platform with the advantage that a large number of genes can be analyzed simultaneously and that too of multiple patients in a single run. 5,24 It is a rapidly evolving field and studies have shown its effectiveness in salivary gland tumor cytology. 24,25 However, the major limitations are the high cost and requirement of robust bioinformatics to handle the analysis and interpretation of large amounts of data.…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Next-generation sequencing (NGS) is a relatively new high-throughput, highly sensitive molecular technology platform with the advantage that a large number of genes can be analyzed simultaneously and that too of multiple patients in a single run. 5,24 It is a rapidly evolving field and studies have shown its effectiveness in salivary gland tumor cytology. 24,25 However, the major limitations are the high cost and requirement of robust bioinformatics to handle the analysis and interpretation of large amounts of data.…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
“…5,24 It is a rapidly evolving field and studies have shown its effectiveness in salivary gland tumor cytology. 24,25 However, the major limitations are the high cost and requirement of robust bioinformatics to handle the analysis and interpretation of large amounts of data. 26 SalvGlandDx is an all-in-one RNA-based NGS panel that detects mutations, fusions, and gene expression levels of 27 genes (including NR4A3) found in salivary gland tumors.…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
“…Indeed, NGS yielded a sensitivity and a specificity of 71% and 94%, respectively. Notably, only 4/14 malignant cases showed no alterations, whereas only 1/18 benign lesions showed a mutation 35 . Fumagalli et al highlighted the suitability of NGS for breast cancer ( BRCA ) 1/2 gene analysis on cytological samples derived from neoplastic ascites of ovarian cancer patients.…”
Section: Clinical Application Of Ngs To Cytological Samplesmentioning
confidence: 99%
“…Notably, only 4/14 malignant cases showed no alterations, whereas only 1/18 benign lesions showed a mutation. 35 Fumagalli et al highlighted the suitability of NGS for breast cancer ( BRCA ) 1/2 gene analysis on cytological samples derived from neoplastic ascites of ovarian cancer patients. In this study, NGS of cytological samples showed a success rate of 100.0%.…”
Section: Clinical Application Of Ngs To Cytological Samplesmentioning
confidence: 99%
“…[6][7][8][9][10] In contrast, NGS is only rarely used by cytopathologists for salivary glands aspirates. 6,8,[11][12][13][14] Moreover, the choice of the ancillary technique test depends largely on the institution's budget, available platforms, and expertise of trained staffs. However, NGS is a promising approach to facilitate the diagnosis and classification of salivary gland tumors.…”
Section: Introductionmentioning
confidence: 99%